Surgical removal of upper right third molar: case report (Research, Society and Development, 2022)
The aim of the present study was to report a clinical case of surgical extraction of an erupted upper right third molar. A 28 years old normoactive male patient, with leukoderma, attended the school clinic of the Faculty of Dentistry Instituto de Ensino Superior e Pós Graduação Padre Gervásio – INAPÓS, looked for a treatment of tooth number 18, after his authorization through the Free and Informed Consent Term, the treatment began. During the anamnesis, the patient's main complaint was dissatisfaction with the aesthetics of his teeth and gingival bleeding. Clinical exams were also performed, with panoramic radiography being the choice in this case; and after evaluating all the information obtained by these exams, the extraction of tooth 18 was indicated, since it had a carious lesion and gingival inflammation, thus supporting the therapeutic approach taken. For this case, the selected method consisted of extraction using the alveolar approach, since the tooth #18 had a favorable root morphology and position for this technique. The excision was performed using the straight and lateral Seldin extractors using technique 2 as noble instruments, in addition to the 18 R forceps with technique I, which were able to promote complete dislocation of the tooth in a more conservative manner. It was possible to conclude that it is important to perform clinical and auxiliary examinations by the dentist, in which the correct indication for a less traumatic technique produced satisfactory results.